Thyroid storm with delayed hyperbilirubinemia and severe heart failure: indication and contraindication of plasma exchange. (4th September 2020) - Nakao, Tomomi; Takeshima, Ken; Ariyasu, Hiroyuki; Kurimoto, Chiaki; Uraki, Shinsuke; Morita, Shuhei; Furukawa, Yasushi; Iwakura, Hiroshi; Akamizu, Takashi
Abstract : Summary: Thyroid storm (TS) is a life-threatening condition that may suffer thyrotoxic patients. Therapeutic plasma exchange (TPE) is a rescue approach for TS with acute hepatic failure, but it should be initiated with careful considerations. We present a 55-year-old male patient with untreated Graves' disease who developed TS. Severe hyperthyroidism and refractory atrial fibrillation with congestive heart failure aggregated to multiple organ failure. The patient was recovered by intensive multimodal therapy, but we had difficulty in introducing TPE treatment considering the risk of exacerbation of congestive heart failure due to plasma volume overload. In addition, serum total bilirubin level was not elevated in the early phase to the level of indication for TPE. The clinical course of this patient instructed delayed elevation of bilirubin until the level of indication for TPE in some patients and also demonstrated the risk of exacerbation of congestive heart failure by TPE. Learning points: Our patient with thyroid storm could be diagnosed and treated promptly using Japan Thyroid Association guidelines for thyroid storm. Delayed elevation of serum bilirubin levels could make the decision of introducing therapeutic plasma exchange difficult in cases of thyroid storm with acute hepatic failure. The risk of worsening congestive heart failure should be considered carefully when performing therapeutic plasma exchange.